Exercise and exerkines: Mechanisms and roles in anti-aging and disease prevention - Xuan Lu; Ying Chen; Yue Shi; Yi Shi; Xianbin Su; Peijie Chen; Die Wu; Hui Shi (Experimental Gerontology)
Aging is a complex biological process characterized by increased inflammation and susceptibility to various age-related diseases, including cognitive decline, osteoporosis, and type 2 diabetes. Exercise has been shown to modulate mitochondrial function, immune responses, and inflammatory pathways, thereby attenuating aging through the regulation of exerkines secreted by diverse tissues and organs. These bioactive molecules, which include hepatokines, myokines, adipokines, osteokines, and neurokines, act both locally and systemically to exert protective effects against the detrimental aspects of aging. This review provides a comprehensive summary of different forms of exercise for older adults and the multifaceted role of exercise in anti-aging, focusing on the biological functions and sources of these exerkines. We further explore how exerkines combat aging-related diseases, such as type 2 diabetes and osteoporosis. By stimulating the secretion of these exerkines, exercise supports healthy longevity by promoting tissue homeostasis and metabolic balance. Additionally, the integration of exercise-induced exerkines into therapeutic strategies represents a promising approach to mitigating age-related pathologies at the molecular level. As our understanding deepens, it may pave the way for personalized interventions leveraging physical activity to enhance healthspan and improve quality of life.